2016
DOI: 10.1016/j.celrep.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Zika Virus and Dengue Virus Dependency Factors using Functional Genomics

Abstract: The flaviviruses dengue virus (DENV) and Zika virus (ZIKV) are severe health threats with rapidly expanding ranges. To identify the host cell dependencies of DENV and ZIKV, we completed orthologous functional genomic screens using RNAi and CRISPR/Cas9 approaches. The screens recovered the ZIKV entry factor AXL as well as multiple host factors involved in endocytosis (RAB5C and RABGEF), heparin sulfation (NDST1 and EXT1), and transmembrane protein processing and maturation, including the endoplasmic reticulum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
343
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(357 citation statements)
references
References 50 publications
13
343
1
Order By: Relevance
“…Recent CRISPR-Cas9-based screenings have confirmed the importance of these groups of host proteins, most of which are directly associated with the ER function (47,48). Among these genes, SPCS1 and SPCS3 are signal peptidases which convert secretory and some membrane proteins to their mature forms by cleaving their signal peptides from their N termini; SEC61B and SEC63 are part of the SEC61 complex, which mediates protein translocation across the ER; STT3A is the catalytic subunit of the N-oligosaccharyltransferase (OST) complex, which catalyzes N-linked glycosylation; and SSR3 is a glycosylated ER membrane receptor associated with protein translocation across the ER membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent CRISPR-Cas9-based screenings have confirmed the importance of these groups of host proteins, most of which are directly associated with the ER function (47,48). Among these genes, SPCS1 and SPCS3 are signal peptidases which convert secretory and some membrane proteins to their mature forms by cleaving their signal peptides from their N termini; SEC61B and SEC63 are part of the SEC61 complex, which mediates protein translocation across the ER; STT3A is the catalytic subunit of the N-oligosaccharyltransferase (OST) complex, which catalyzes N-linked glycosylation; and SSR3 is a glycosylated ER membrane receptor associated with protein translocation across the ER membrane.…”
Section: Discussionmentioning
confidence: 99%
“…PKI 14-22 does not interfere with host translation machinery to inhibit ZIKV replication. By screening genes essential for ZIKV replication using the clustered regularly interspaced short palindromic repeat (CRISPR) technology, previous studies have identified several host genes that play vital roles in regulating ZIKV replication (47,48). Most of these genes are endoplasmic reticulum (ER) associated and functionally related to protein translation and modification.…”
Section: Pki 14-22 Inhibits Zikv Replication By Inhibiting the Pka Pamentioning
confidence: 99%
“…Whereas Gas6 binds to all three TAM family members with high affinity, protein S binds to TYRO3 and MERTK, but not to AXL (17). The TAM receptor AXL was recently shown to support ZIKV infection of human foreskin fibroblasts (12), and its expression was noted in the brain and neuroprogenitor cells (18)(19)(20)(21). However, its deletion had no effect on ZIKV infection of induced pluripotent human stem cell-derived neuroprogenitor cells or cerebral organoids (22) or on virus accumulation of the eye, brain, or testis in Axl −/− mice (23,24).…”
mentioning
confidence: 99%
“…This is largely due to the varied efficiency of multiple steps of entry leading to productive infection. Whereas multiple host factors are involved in late post-fusion steps of virus entry (1)(2)(3)(4)(5)(6)(7)(8)(9), the effects of intrinsic, cell type-dependent factors and extrinsic factors on viral fusion are poorly characterized. After the initial interaction of viruses with cellular receptors or attachment factors, low endosomal pH is required to trigger fusion-inducing conformational changes in most viral proteins (reviewed in Refs.…”
mentioning
confidence: 99%